Применение схемы гибкой нити для расчета перекрытий при аварийном отказе колонны - Yury Vasilyevich Krasnoshchekov; Svetlana Olegovna Melnikova (Вестник СибАДИ)
The results of the study of multi-storey buildings with a carrying capacity of Svjaseva frame with a crash of one of the columns. Two variants of strengthening of precast concrete slabs in order to prevent progressive collapse. For static and dynamic analysis of reinforced slab design scheme of flexible filaments used. Examples of calculation of the building on the progressive collapse.